ECT in schizophrenia: a review of the evidence. Issue 3 (3rd December 2018) - Grover, Sandeep; Sahoo, Swapnajeet; Rabha, Anjumoni; Koirala, Raman
Abstract: Electroconvulsive therapy (ECT) was initially used for the treatment of schizophrenia, but over the years with the advent of antipsychotics, its use in schizophrenia has been limited. Treatment guidelines vary in their recommendations for the use of ECT in schizophrenia. The usual indications of its use among patients with schizophrenia include treatment resistance, to augment pharmacotherapy, to manage catatonia, suicidal behaviour, severe agitation and clozapine-resistant schizophrenia. Available literature, including meta-analysis and systematic reviews, suggest that ECT is a safe and effective treatment in patients with schizophrenia. However, despite the available evidence, it is highly underutilised and is often used as one of the last resort among patients with schizophrenia. This review focuses on the indications of use of ECT in schizophrenia, studies evaluating its effectiveness, efficacy in certain special situations like first episode schizophrenia, adolescents, catatonia etc., predictors of response to ECT in schizophrenia and influence of various ECT-related parameters on efficacy/effectiveness among patients with schizophrenia. From the review, it can be concluded that ECT is not only is beneficial as an augmenting strategy in treatment-resistant schizophrenia but also can be used effectively in patients with schizophrenia in various other situations.